A new case of SMABF2 diagnosed in stillbirth expands the prenatal presentation and mutational spectrum of ASCC1. Issue 3 (27th December 2019) - Giuffrida, Maria G.; Mastromoro, Gioia; Guida, Valentina; Truglio, Mauro; Fabbretti, Maria; Torres, Barbara; Mazza, Tommaso; De Luca, Alessandro; Roggini, Mario; Bernardini, Laura; Pizzuti, Antonio
Abstract: Spinal muscular atrophy with congenital bone fractures 2 (SMABF2) is a rare autosomal recessive neuromuscular disorder characterized by arthrogryposis multiplex congenita and prenatal fractures of the long bones, with poor prognosis. The most affected patients present with biallelic loss‐of‐function nucleotide variants in ASCC1 gene, coding a subunit of the transcriptional coactivator ASC‐1 complex, although the exact pathogenesis is yet unknown. This work describes the first case of SMABF2 in a stillbirth with documented evolution of the disease in the prenatal period. A microdeletion copy number variant (CNV) of about 64 Kb, involving four exons of ASCC1, was firstly detected by microarray analysis, requested for arthrogryposis and hydrops. Subsequent exome analysis disclosed a nucleotide variant of the same gene [c.1027C>T; (p. Arg343*)], resulting in the introduction of a premature termination codon. This stillbirth represents the first case of ASCC1 compound heterozygosity, due to an exonic microdeletion and a nucleotide variant, expanding the mutational spectrum of this gene. It also provides further evidence that exonic CNVs are an underestimated cause of disease‐alleles and that the integrated use of the last generation genetic analysis tools, together with careful clinical evaluations, are fundamental for the characterization of rare diseases even in the prenatal setting.